2011
DOI: 10.1590/s1806-37132011000200007
|View full text |Cite
|
Sign up to set email alerts
|

Sintomas indicativos de disfagia em portadores de DPOC

Abstract: Objective: To identify symptoms of dysphagia in individuals with COPD, based on their responses on a selfperception questionnaire. Methods: The study comprised 35 individuals with COPD and 35 healthy individuals, matched for age and gender. The study group was assessed regarding COPD severity; sensation of dyspnea; body mass index (BMI); and symptoms of dysphagia. The control group was assessed regarding BMI and symptoms of dysphagia. Results: The most common symptoms of dysphagia in the study group were phary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 28 publications
(36 reference statements)
0
14
0
9
Order By: Relevance
“…This is the only investigation known to the authors that attempts to define dysphagia in a population of COPD patients who were also underweight. Prior research has reported on BMI but not limited inclusion to those patients presenting with low BMI 9,16. Further, we detailed oral intake, patient-reported symptoms of swallowing impairment, and the impact of dysphagia on quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…This is the only investigation known to the authors that attempts to define dysphagia in a population of COPD patients who were also underweight. Prior research has reported on BMI but not limited inclusion to those patients presenting with low BMI 9,16. Further, we detailed oral intake, patient-reported symptoms of swallowing impairment, and the impact of dysphagia on quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Malnutrition is due to decreased food intake, but mostly to a higher resting metabolic rate [6]. Dysphagia is usually a precipitating factor for malnutrition [7-10]. To date, little attention has been given to the investigation of swallowing disorders in patients with COPD.…”
Section: Introductionmentioning
confidence: 99%
“…João Rafael Sauzem Machado (1) , Eduardo Matias dos Santos Steidl (1) , Diego Fernando Dorneles Bilheri (1) , Mateus Trindade (2) , Guilherme Lopes Weis (2) , Paulo Roberto Oliveira de Jesus (3) , Marisa Bastos Pereira (4) , Renata Mancopes (5) (1) Universidade Federal de Santa Maria, RS -Brasil. 2) Serviço de Radiologia do Hospital Universitário de Santa Maria, RS -Brasil.…”
Section: Efeitos Do Exercício Muscular Respiratório Na Biomecânica Daunclassified
“…Besides being the act of conducting food or substances in the oral cavity to the stomach, in a safe way (by protecting the airway against aspiration), it represents a temporal integration of events associated with normal breathing 1 . In healthy subjects, breathing is interrupted during swallowing.…”
Section: Departamento De Fonoaudiologia -Programa De Pós-graduação Emmentioning
confidence: 99%